Profit efficiency development of Islamic Banking using the stochastic frontier approach - Nasution, Zubaidah (Jurnal Ekonomi & Keuangan Islam, 2020)
This study aims to analyze the efficiency of Islamic banking with a stochastic frontier analysis (SFA) on 10 Islamic banks from 2011 to 2018. The research variables consist of input variables total profits, third party funds and personnel expenses and output variable total financing and murabahah receivables. This research method uses SFA to measure the efficiency of Islamic banks and the influence between variables. The results of this study indicate the average efficiency of Islamic banks has not reached 100% or at 82.24%. Variable third party funds, personnel expenses have a positive effect on total profits while total financing and murabahah receivables have a negative effect on total profits.